ANALISIS KOMUNIKASI MATEMATIS TERHADAP SANTRI DALAM PEMBELAJARAN MATEMATIKA DENGAN MODEL COOPERATIVE SCRIPT - Prihanto, Adnan; Mayasari, Novi (IKIP PGRI Bojonegoro, 2022)
Abstract: The purpose of this study was to describe (1) the communication style of students in the cooperative Script model of mathematics learning, (2) the oral and written mathematical communication skills in the cooperative Script model of mathematics learning. This study involved 10 students of class VIII B SMP Muhammadiyah Cepu Foundation Modern Islamic Boarding School Cepu Muhammadiyah Boarding School 2021/2022. Data collection techniques used are observation, written test, and interview. The estimation of the validity of this instrument is tested by the validator and for analysis the test uses the Aiken formula, the reliability uses CronBach's Alpha, and the level of difficulty and distinguishing power is tested. The data analysis techniques used are (1) data reduction, (2) data presentation, (3) conclusion raising. The results showed that (1) the communication style of the students was The Equalitarium Style. (2) the mathematical communication skills of students orally in the cooperative Script model of mathematics learning are included in the high and low categories, while the students' communication skills in the cooperative Script model mathematics learning are included in the low and high categories.Keywords communication;style; writing; oral; Students.